2021
DOI: 10.1186/s12905-021-01329-x
|View full text |Cite|
|
Sign up to set email alerts
|

Necessity for subsequent surgery in women of child-bearing age with positive margins after conization

Abstract: Background 20–25% of women with high-grade cervical intraepithelial neoplasias (HSIL) have residual lesions after conization. The state of the margin is generally considered to be a risk factor for recurrence or persistent lesions. Predictors of positive margins and residual lesions need to be identified. A design for postoperative management and avoidance of overtreatment needs to be provided, especially for women of child-bearing age. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…Here, the age of 35 y was also taken as the boundary to separate the age of menopause as this age group is of childbearing age and had one of the highest incidences of cervical lesions. We also found that age >35 y was a risk factor for positive margins after LEEP surgery (P = 0.033), which is consistent with the previous results (25). Previous studies showed that menopause was a risk factor for positive surgical margins (26,27), and our research also confirmed these findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, the age of 35 y was also taken as the boundary to separate the age of menopause as this age group is of childbearing age and had one of the highest incidences of cervical lesions. We also found that age >35 y was a risk factor for positive margins after LEEP surgery (P = 0.033), which is consistent with the previous results (25). Previous studies showed that menopause was a risk factor for positive surgical margins (26,27), and our research also confirmed these findings.…”
Section: Discussionsupporting
confidence: 92%
“…At present, TCT and ECC are mainly used for cervical cancer screening and diagnosis, but their impact on prognosis is often ignored clinically. Patients with higher cytological atypia also have a higher probability of positive margins and residual lesions ( 25 ). Here, our study emphasizes the importance of preoperative cytological results for patient evaluation.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Studies have found that age, menopausal status, and abnormal cytological testing are common risk factors for positive margins. 21 However, in our study, abnormal cytological testing and pathological margins were not associated with HPV infection status. Debaudrap et al 22 did a meta-analyses, showed that in the treatment of cervical precancerous lesions in HIV infected women, the failure rate of treatment with positive margins (47.2%, 95% CI 22.0–74.0) was significantly higher than that of patients with negative margins (19.4%, 95% CI 11.8–30.2).…”
Section: Discussioncontrasting
confidence: 70%
“…Margin involvement is regarded as an important predictor of residual disease [ 5 , 14 , 26 ]. Repeated cervical conization is considered an acceptable alternative for women with a positive cone margin who desire fertility preservation, and hysterectomy is the definitive therapy for women with no reproductive requirements [ 27 , 28 ]. If the choice of treatment is new conization or hysterectomy, most women will unnecessarily undergo these procedures because they have no residual lesions.…”
Section: Discussionmentioning
confidence: 99%